Formulation and Physicochemical Characteristics and Acceptability of an Enteral Formula Based on Catfish, Soybean, and Purple Sweet Potato for Pregnant Women with Chronic Energy Deficiency (CED) - Khoiriyah, Nafisa Fida'ul; Intifadah, Darin Syahidah; Mustikaningrum, Fitriana (Rifa'Institute, 2026)
Introduction: Chronic Energy Deficiency in pregnant women requires energy-dense nutritional interventions to support maternal and fetal health. One potential approach is the development of locally sourced enteral formulas with adequate nutritional and physicochemical properties.Objective: This study aimed to evaluate the physicochemical characteristics and sensory acceptability of a modified enteral formula based on catfish, soybeans, and purple sweet potatoes. Method: This experimental study compared two formulations, formulation A with soybean dominance and formulation B with catfish dominance, against a commercial control. The evaluation included measurements of energy density, viscosity, flow rate, acidity level, osmolarity, and sensory acceptability. Result and Discussion: The results showed that the modified formulas successfully achieved a high energy density of 1.2 kilocalories per milliliter. Both formulations showed ideal viscosity ranging from 31.45 to 36.39 centipoise, appropriate flow rate, and neutral acidity level suitable for nasogastric tube application, although both were categorized as hyperosmolar with values above 700 milliosmoles per liter. In the sensory evaluation, formulation A was significantly preferred over formulation B, particularly in texture and taste. The dominance of soybean protein in formulation A produced a smoother liquid consistency and effectively masked the fishy aftertaste found in formulation B. Conclusions: Formulation A is recommended as the most potential local food-based enteral formula prototype for pregnant women with chronic energy deficiency, although further optimization is needed to reduce its osmolarity level